THE ASSOCIATION BETWEEN TRUST IN PHYSICIAN AND PREVENTIVE HEALTHCARE UTILIZATION: FINDINGS FROM THE PINE STUDY. (11th November 2018) - Liu, A; Bergren, S; Li, M; Dong, X
Abstract: Trust in physician (TIP) is seen as a vital component of healthcare, especially among minority populations, but little is known about its relationship to preventive healthcare utilization. This study aims to examine the association between TIP and preventive healthcare utilization among U.S. Chinese older adults. Data were drawn from the Population Study of Chinese Elderly in Chicago (PINE), a sampling of 3, 157 community-dwelling U.S. Chinese older adults age 60 and above. TIP was measured by 11-item Trust in Physician scale from Anderson and Dedrick. Logistic regressions were used to examine the association between TIP and preventive healthcare utilization: recent vaccination (flu, pneumonia, hepatitis B), and lifetime cancer screenings (colon cancer, breast cancer, cervical cancer, prostate cancer). Results showed that every one-point increase in TIP (range: 11–55) were significant associated with 4% increased likelihood of flu vaccine (OR: 1.04[1.03, 1.06]), 3% increased likelihood of pneumonia vaccine (OR: 1.03[1.02, 1.05]), and 3% increased likelihood of colon cancer screening (OR: 1.03[1.01, 1.04]). However, no associations were found between TIP and utilization of hepatitis B vaccination and breast, cervical, and prostate cancer screenings. Study results add to the evidence that higher level of TIP was associated with higher utilization rate of some types of preventive healthcare. Inconsistent with previous studies, non-significant associations were found between TIP and some types of preventive healthcare, which call for further examination. Preventive healthcare utilization remains low among immigrant minority populations, and study findings support a need for tailored intervention strategies.